The acceptance and awareness of smallholder on the mean of controlling of Oryctes sp. in relation to agronomic practices to suppress pest abundance in oil palm plantation / Mohd Izzanur Rashidi - Rashidi, Mohd Izzanur (Faculty of Plantation and Agrotechnology, 2017)
The growth of the oil palm industry has becoming more developed with the use of proper agronomic practices in a favorable plantation environment. The main problems which had been arise were being identified from the smallholder which is known to be lack of fundamental knowledge and exposure regarding agronomic practices as they are known to be managing their own farm by self-financing in order to obtain yield from the oil palm. In general, they could not manage to obtain higher yield due to their current position which also relates with the lack of knowledge in term of controlling the pest infestation in their farm. This survey study was carried out by distributing the questionnaire for the smallholder in order to assess their acceptance and awareness towards the agronomic practices on controlling the Oryctes rhinoceros. The methods of analysis used in this study were the Descriptive analysis, Correlation test and Regression analysis in order to identify the relationship between the productivity yield with the acceptance and awareness of the smallholder towards the agronomic practices in controlling the rhinoceros beetle. As conclusions, the smallholder need to be more exposure towards new technology and open-minded in term of accepting and aware of new things for their plantation productivity and at the same time by implementing the agronomic practices which had been outlined by the industry in order to reduce the pest attack and increase yield significantly.